Walter Benjamin and Theology - Symons, Stephane; Dickinson, Colby (Book collections on Project MUSE., 2016)
Benjamin's relationship to theological matters has been less observed than it should. Walter Benjamin and Theology brings together some of the world's most renowned experts to reassess the stake theology has in Benjamin's writings, aiming for nothing less than the beginning of a new phase in Anglophone Benjamin scholarship.